2021
DOI: 10.1002/jcla.23999
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor gene polymorphisms (SNP ‐173 G>C and STR‐794 CATT5‐8) confer risk of plaque psoriasis: A case–control study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…MIF is a key proinflammatory cytokine that plays a role in inflammation, autoimmune, metabolic diseases, and cancer. 27 In recent years, the MIF rs755622(−173G/C) polymorphism has been shown to be associated with the pathogenesis and progression of autoimmune diseases, such as rheumatoid arthritis (RA), 28 psoriasis, 29 systemic sclerosis (SSc), 30 and systemic lupus (SLE). 31 A study in a population of western Mexicans confirmed a significant association between MIF gene polymorphisms (−794CATT5-8 and −173G/C) and NSV.…”
Section: Discussionmentioning
confidence: 99%
“…MIF is a key proinflammatory cytokine that plays a role in inflammation, autoimmune, metabolic diseases, and cancer. 27 In recent years, the MIF rs755622(−173G/C) polymorphism has been shown to be associated with the pathogenesis and progression of autoimmune diseases, such as rheumatoid arthritis (RA), 28 psoriasis, 29 systemic sclerosis (SSc), 30 and systemic lupus (SLE). 31 A study in a population of western Mexicans confirmed a significant association between MIF gene polymorphisms (−794CATT5-8 and −173G/C) and NSV.…”
Section: Discussionmentioning
confidence: 99%